Synthesis of Oxovanadium(IV) Schiff base Complexes derived from C-substituted Diamines and Pyridoxal-5-Phosphate as Antitumor Agents - Hazari P.P.; Pandey A.K.; Chaturvedi S.; Tiwari A.K.; Chandna S.; Dwarakanath B.S.; Mishra A.K. (My University, 2025)
Oxovanadium (IV) complexes of N,N'-bispyridoxyl-5, 5'-bis (phosphate) ethylenediimine (L1) and N,N'-bis(pyridoxyl)-5,5'-bis(phosphate)-1''-(p-nitrobenzyl)ethylenediimine (L2) were synthesized by condensation of optically active C-substituted diamines and pyridoxal-5-phosphate. Oxovanadium (IV) complexes derived from L1 and L2 were evaluated as DNA cleavage agent (cleavage of supercoiled plasmid pBR322 DNA). Interestingly, both the oxovanadium (IV) complexes exhibited DNA nuclease activity, and the extent of oxidation of DNA by these vanadyl complexes was superior to VOSO 4. The significant reduction in primary tumor and increased delay in tumor growth of 15days was seen in the tumor regression analysis with oxovanadium (IV) complex of L1. With the preliminary studies performed with the pyridoxal-5-phosphate -based salen derivatives including the cytotoxicity and tumor regression, it is evident that the salen bifunctional chelating agent has obtained therapeutic potential if conjugated to a gene-specific targeting molecule for the oxidation of guanine residue. © 2011 John Wiley & Sons A/S.